Synthesis of SMC algorithms applied to wind generator - Houaria Abdelli; Abdelkader Mezouar; Mokhtar Bendjebbar; Kheira Belgacem (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The use of the classical (SMC) applied to control of stator’s powers of DFIG, gives the problem of chattering, therefore to avoid this phenomenon a robust algorithm (STSMC) is applied. This paper presents a comparison of conventional SMC with the proposed strategy of STSMC algorithm. The results are obtained using MATLAB and demonstrate stability and robustness of this algorithm.